Roncarelli v. Duplessis and Damages for Abuse of Power: For What Did It Stand in 1959 and For What Does It Stand in 2009? - Mullan, David (McGill Law Journal / Revue de droit de McGill, 2010)
Today, Roncarelli v. Duplessis is most celebrated for the contributions that Justice Rand’s judgment in particular made to a rule of law—based conception of the exercise of discretionary power. However, from a contemporary perspective, the Supreme Court of Canada’s decision was seen not only as another significant judicial reining in of the Duplessis government’s treatment of Jehovah’s Witnesses, but also as an important development in the law governing governmental liability for abuse of power.In this paper, the author explores the latter dimension of the judgment with a view to establishing the grounds on which the Court found Duplessis personally liable in damages to Roncarelli, and the extent to which it transcended the particular provision on which liability was based (article 1053 of the Civil Code of Lower Canada) and had application at common law. He also evaluates the subsequent impact of this aspect of the judgment. How have later courts read the judgment’s articulation of the principles of delictual liability, and what are the current principles on which the liability of state actors for abuse of power are based? Here too, the author concludes that the current state of the law is closer to that espoused by Justice Rand than the bases on which the other members of the majority predicated liability.